COURSE ASSESSMENT IN THE DISTANCE MODE BY UNDERGRADUATE STUDENTS OF NURSING - Ana Luísa Petersen Cogo; Gabriela Petró Valli Czerwinski; Débora Marie da Silva Bonmann; Jamile Araujo Durlo; Karema da Conceição Pereira (Universidade Federal do Paraná, 2015)
The study aimed to analyze the development of the 'Nursing and Research' course in the distance mode of the Undergraduate Course in Nursing, characterizing the similarities and the differences in relation to the on-site teaching. It had a quantitative approach of the exploratory descriptive type, and was undertaken with 60 students of the on-site course and 53 of the distance learning course at a public university in the state of Río Grande do Sul. Data collection took place in 2012 and 2013, through a questionnaire and data from the virtual environment, analyzed using descriptive statistics (level of significance of 5%). The students from the distance learning groups presented a higher proportion of professionalization in comparison with the on-site groups (p=0.007). Communication using email was predominant, with 266 messages sent requesting clarification regarding exercises. It is concluded that there is similarity in the groups' evaluations of the two modes of teaching, with the distance mode being an alternative for students who work.